Colorectal Cancer: The Impact of Smoking and Alcohol on Risk in West Nusa Tenggara, Treatment, and Prevention - Arif Zuhan; Syakir, Syahda Aqila (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
: Colorectal cancer (CRC) is the third most common cancer globally and the second leading cause of cancer-related mortality. It results from complex interactions between genetic, environmental, and lifestyle factors, with smoking and alcohol consumption being significant contributors. This study focuses on the correlation between smoking and alcohol consumption with CRC incidence in West Nusa Tenggara (NTB), a province in Indonesia known for its high smoking prevalence (32.79%) and alcohol consumption rate (1.6%). A literature review methodology was employed, systematically collecting data from PubMed, ScienceDirect, Cochrane Library, Google Scholar, and ProQuest using keywords such as